Congenital uterovaginal abnormalities, it's embryogenesis, surgical management and clinical implications - Krishna Gopal Paul; Kalyan Chakravarthi Kosuri; Hasam Bayad (Korean Society of Obstetrics and Gynecology, 2020)
Objective Congenital Mullerian duct malformations are a challenging group of conditions for surgeons and need surgical experience and skill. Accordingly, the aim of this study is to present the diagnosis, surgical management, and clinical implications of congenital uterovaginal abnormalities. Methods Between 1980 and 2015, 8 patients with congenital uterovaginal abnormalities were diagnosed. In one patient a unique case of an unusual horseshoe shaped double uterus communicating via a transverse canal along with agenesis of the cervix and vagina was noted, and utero-vaginal agenesis was diagnosed in 6 patients. Complete androgen insensitivity syndrome with its female phenotype associated with bilateral testicular tissue in the inguinal canal with an accompanying absence of the ovaries, uterus, uterine tubes, vagina, and an imperforate hymen, was diagnosed in one patient. Clinical examination of all the patients revealed well-developed secondary sexual characteristics. A modified McIndoe vaginoplasty procedure was the surgical treatment common to all patients to treat vaginal agenesis. The surgery was performed by a consultant (Dr. K.G. Paul) using the standardized surgical technique. Results An unusual Mullerian duct anomaly, uterus bicornisacollis, was successfully corrected by uteroplasty and a new cervix was constructed. Complete vaginal agenesis was corrected by a modified McIndoe vaginoplasty technique. None of the patients had any significant post-operative complications. Conclusion Knowledge of congenital uterovaginal abnormalities diagnosed in this study is essential for surgeons, clinical anatomists, radiologists, and morphologists who may increase the success of their diagnostic evaluations and surgical approaches to the region.